2021
DOI: 10.1108/arch-11-2020-0260
|View full text |Cite
|
Sign up to set email alerts
|

Open space and sense of community of older adults: a study in a residential area in Hong Kong

Abstract: PurposeThis study examines the relationship between quality and quantity of open space in residential areas and the sense of community of Chinese older adults in Hong Kong.Design/methodology/approachA survey was conducted with 257 adults aged 55 and over in Kwun Tong, Hong Kong. The quality of open space was assessed from four dimensions: social and recreational facilities, entrance, location and environment. Geographic information system (GIS) was used to evaluate the quantity of open space in terms of size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Open spaces, including parks and gardens, are an essential part of a network of physical and social wellbeing. In this regard, two studies on Chinese older adults confirmed that psychological wellbeing was influenced by the quality of open space, and was positively correlated with walkable environment, and, in particular, with the perceived attributes of accessibility and walking facilities [ 24 , 25 ]. Parks not only provide space to exercise but also allow their user to overcome mental isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Open spaces, including parks and gardens, are an essential part of a network of physical and social wellbeing. In this regard, two studies on Chinese older adults confirmed that psychological wellbeing was influenced by the quality of open space, and was positively correlated with walkable environment, and, in particular, with the perceived attributes of accessibility and walking facilities [ 24 , 25 ]. Parks not only provide space to exercise but also allow their user to overcome mental isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study pointed out that the quality and quantity of facilities for recreational activity affects the level of social mixing and therefore the sense of community. The quality of green space is associated to opportunities of social interactions and cohesion for some studies, namely, those conducted in Hong Kong [89] or in Turkey [90] in relation to a sense of neighbourhood attachment. This causal link is unsolved in the literature, as emphasised by Yu [89].…”
Section: The Social Nature Of Green Space Usementioning
confidence: 99%
“…The quality of green space is associated to opportunities of social interactions and cohesion for some studies, namely, those conducted in Hong Kong [89] or in Turkey [90] in relation to a sense of neighbourhood attachment. This causal link is unsolved in the literature, as emphasised by Yu [89]. His study demonstrates the relevance of quality of the environment, rather than quantity of facilities; nevertheless, this result is acknowledged to be inconsistent with other similar studies, thus deserving further investigation.…”
Section: The Social Nature Of Green Space Usementioning
confidence: 99%
“…Engagement can satisfy human needs for leisure and spirituality by providing the long-term impacts of recreation, relaxation and tranquillity (Carr et al , 2007; Costanza et al , 2007; Haq, 2011; Lee et al , 2015; Matsuoka and Kaplan, 2008). Engaging with nature and other people affect respect, receptiveness and passion, and give a sense of belonging, all reflected in affection, participation and identity needs (Costanza et al , 2007; Matsuoka and Kaplan, 2008; Max-Neef, 1991; Salih et al , 2020; Yu, 2021).…”
Section: The Public Park Systemmentioning
confidence: 99%